2020
DOI: 10.1123/iscj.2018-0044
|View full text |Cite
|
Sign up to set email alerts
|

Coaching Strategies Used to Deliver Quality Youth Sport Programming

Abstract: Coaches are primary influencers in helping youth achieve positive developmental outcomes in sport; however, it is not well understood how coaches achieve quality program delivery. The purpose of this study was two-fold: (a) to understand strategies that coaches used to facilitate program quality in youth sport and (b) explore differences in strategies between recreational and competitive programs. Twenty-five coaches participated in semistructured interviews, where they discussed strategies employed for progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…27 All youth sport coaches should consider how they can create a sporting environment where youth feel comfortable to be themselves and feel safe in taking risks to support positive identity experiences (e.g., providing supervision in locker room areas, performing safety checks for hazards in the environment, encouraging youth to approach them when they have concerns, checking-in with youth as they enter the program area, speaking to youth as humans first and athletes second). 10 However, these results are not conclusive; researchers need to consider exploring racial/ and/or ethnic differences within youth sport contexts, as such explorations are currently lacking. 38 Third, F-tests showed that recreational teams scored higher on opportunities to belong (PAQYS) and choice (BNSSS) compared to competitive.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…27 All youth sport coaches should consider how they can create a sporting environment where youth feel comfortable to be themselves and feel safe in taking risks to support positive identity experiences (e.g., providing supervision in locker room areas, performing safety checks for hazards in the environment, encouraging youth to approach them when they have concerns, checking-in with youth as they enter the program area, speaking to youth as humans first and athletes second). 10 However, these results are not conclusive; researchers need to consider exploring racial/ and/or ethnic differences within youth sport contexts, as such explorations are currently lacking. 38 Third, F-tests showed that recreational teams scored higher on opportunities to belong (PAQYS) and choice (BNSSS) compared to competitive.…”
Section: Discussionmentioning
confidence: 99%
“…Higher ratings of belongingness may be explained by the shared spaces common to recreational contexts, as they often offer exposure to positive emotional climates (e.g., using respectful language, zero tolerance of bullying). 39 As recreational sport is commonly engaged in for enjoyment and inclusivity, 5 belonging may also exist as an inherent consequence of recreational structures; 10 whereas competitive sport that values winning may be more tolerant of punitive climates facilitated from reactions of failure to meet performance or characterrelated expectations. 40 As peers (i.e., teammates) play in important role in supporting youth's competence and relatedness, 18 coaches can support youth's sense of belonging by highlighting every athletes' importance or role on the team, encouraging youth to spend time together, and facilitating opportunities for social connection and mentorship.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations